Pengaruh Peran Orang Tua Dan Minat Belajar Terhadap Hasil Belajar Siswa Kelas VI SD Negeri 1 Airmadidi - Rorimpandey, Widdy; Sulastri; Sumampow, Zoya F (Jurnal Elementaria Edukasia, 2023)
Parents are one of the first and foremost educational centers and sources of educators for a student. The role of parents and interest in learning have an important role and influence the quality of achievement of student learning outcomes. This study aims to determine the influence of the role of parents and interest in learning on student learning outcomes. This research was conducted at SD Negeri 1 Airmadidi with the population in the study, namely all grade VI students of SD Negeri 1 Airmadidi totaling 45 sample. Sampling using a nonprobability sampling method. This study used a quantitative research design with multiple regression analysis. The results showed that 1) The role of parents affects student learning outcomes with regression test results obtained sig values of 0.000 < 0.05 which means there is a significant influence, 2) Learning interest affects learning outcomes with regression test results obtained sig values of 0.002 < 0.05 which means there is a significant influence, 3) The role of parents and interest in learning affects learning outcomes with a value of R Square = 0.504 Indicating the role of parents and interest in learning can explain learning outcomes by 50.4% while the remaining 49.6% is influenced by other variables. Thus, this research has implications for helping and facilitating how to maximize student learning by providing quality learning experiences in terms of the role of positive parents and high student learning interest in achieving high learning outcomes as well.